SAT0307 Lesinurad Monotherapy in Gout Patients Intolerant to Xanthine Oxidase Inhibitors (Light): A Randomized, Double-Blind, Placebo-Controlled, 6-Month Phase III Clinical Trial. (9th June 2015) - Tausche, A.-K.; Alten, R.; Dalbeth, N.; Kopicko, J.; Bhakta, N.; Storgard, C.; Baumgartner, S.; Saag, K.
Abstract : Background: Lesinurad (LESU; RDEA594) is a selective uric acid reabsorption inhibitor (SURI) being investigated for the treatment of gout in combination with a xanthine oxidase inhibitor (XOI). Objectives: LIGHT is a multinational randomized, double-blind, placebo-controlled, 6-month phase III clinical trial to determine the efficacy and safety of LESU 400mg monotherapy in patients intolerant to an XOI (NCT01508702 ). Methods: Gout patients with intolerance/contraindication to XOI and serum uric acid (sUA) ≥6.5 mg/dL were randomized to LESU (400mg oral, once daily) or placebo (PBO). The primary endpoint was the proportion of patients with sUA <6.0 mg/dL at Month 6. Safety assessments included treatment-emergent adverse events (TEAEs) and laboratory data. Patients who completed the study were eligible to enroll in an open-label, uncontrolled extension study of LESU 400 mg monotherapy (NCT01650246 ). Results: Patients (LESU, 107; PBO, 107) were primarily white (81.8%) and male (91.1%) with mean ± SD age of 54.4±12.3 years, 11.2±8.7 years since gout diagnosis, 6.2±7.3 gout flares in past 12 months, tophi (25% of patients), renal impairment (58.9% with estimated creatinine clearance [eCrCL] <90 mL/min), and sUA of 9.3±1.5 mg/dL. Patients had intolerance/contraindication to allopurinol (91.1%), febuxostat (8.9%) or both (4.2%). Significantly more patients achieved the primary endpoint (sUA <6.0 mg/dL at Month 6) with LESU 400mg than PBO (29.9% vs.1.9%; Figure ). Discontinuation rate was greater with LESU 400mg (32.7%) than PBO (15.9%). Overall AE rate was higher with LESU 400mg, mainly due to more renal AEs (Table ). Of the 143 patients (PBO, 78; LESU, 65) who enrolled in the extension study, 84 (59%) and 35 (24%) completed 6 and 12 months, respectively, prior to early study termination by the Sponsor (mean LESU exposure, 223 days). A total of 91 patients (64%) achieved sUA <6.0 mg/dL at some point during the extension study. AEs were similar to the LESU 400mg group in the core study (Table ). Conclusions: In this multinational study of gout patients with high sUA and intolerance/contraindication to an XOI, nearly one third of patients treated with LESU 400 mg achieved sUA <6 mg/dL at 6 months. Renal AEs were more frequent with LESU 400mg monotherapy. Acknowledgements: Research sponsored by Ardea Biosciences/AstraZeneca. Editorial support was provided by PAREXEL and funded by AstraZeneca. Disclosure of Interest: A.-K. Tausche Consultant for: Menarini, Ipsen, Novartis, Savient, AstraZeneca, Speakers bureau: Menarini, Ipsen, Novartis, Savient, AstraZeneca, R. Alten Grant/research support from: AstraZeneca, N. Dalbeth Grant/research support from: AstraZeneca, Fonterra, Novartis, Consultant for: AstraZeneca, Fonterra, Takeda, Metabolex, Speakers bureau: Savient, Menarini, Novartis, Takeda, J. Kopicko Employee of: Ardea Bisociences, Inc., a member of the AstraZeneca group, N. Bhakta Employee of: Ardea Bisociences, Inc., a member of the AstraZeneca group, C. Storgard Employee of: Ardea Bisociences, Inc., a member of the AstraZeneca group, S. Baumgartner Employee of: Ardea Bisociences, Inc., a member of the AstraZeneca group, K. Saag Grant/research support from: Ardea/AstraZeneca, Crealta, Takeda, Consultant for: Amgen, Ardea/AstraZeneca, CORONA, Crealta